An Online Pain Education Program for Working Adults: Pilot Randomized Controlled Trial - Li, Yajie; Tse, Mun Yee Mimi (JMIR Publications, 2020)
BackgroundPain is a common public health concern, and the pain situation among the general population is serious in mainland China. Working adults commonly experience pain because of long sitting times, a lack of free time, and exercise. A lack of pain-related knowledge is also a significant factor. Educational and therapeutic programs delivered online were used more often in Western countries, and accessible programs in China are limited, especially for pain management. Therefore, we carried out an online pain education program for working adults to self-manage pain. The program was delivered through WeChat, a popular and secure social media with a large population base in China. ObjectiveThis study aimed to (1) provide pain-related knowledge and self-relief strategies, (2) help participants reduce pain and improve pain-related emotional well-being, and (3) explore participants' learning performance and the acceptability of the online pain education program. MethodsThis was a randomized controlled trial. Chinese adults aged between 16 and 60 years with full-time employment, with pain in the past 6 months, and without any mental illness were recruited using snowball sampling through the internet and were randomly allocated to an experimental group and a control group in 1:1 ratio after the baseline assessment. The 4-week educational program that included basic knowledge of pain, pharmacological and nonpharmacological treatments, and related resources was provided only to the experimental group. Outcomes of pain, depression, anxiety, stress, and pain self-efficacy were measured at baseline (T0), posttreatment (T1), and 1-month follow-up (T2). Participants' acceptability and satisfaction were explored after completing the educational program. ResultsIn total, 95 eligible participants joined in the program: 47 in the experimental group and 48 in the control group. Neck and shoulder, head, and back were most commonly reported pain sites with high pain scores. Pain intensity and interference of the experimental group were significantly reduced after the educational program. Depression, anxiety, and stress clinically improved and pain self-efficacy improved after the educational program. The difference in depression, anxiety, stress, and pain self-efficacy within a group or between groups was not statistically significant; however, clinical improvements were demonstrated. A significant correlation between dosage of the intervention and pain intensity and depression was demonstrated. After completing the educational program, more than half of the participants showed acceptance of and satisfaction with the program, and they were willing to recommend the program to others. ConclusionsOur findings highlight the significant potential of this online education program in the treatment of pain. Trial RegistrationClinicalTrials.gov NCT03952910; https://clinicaltrials.gov/ct2/show/NCT03952910